Inovasi Tpack Dalam Pembelajaran IPAS Kelas 2 SD Negeri 1 Gumul - Ayuna Asri Nurrohmah; Hani Binti Rishadi; Isna Rahmawati (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
Education is an effort made to increase potential, skills, and knowledge both physically and spiritually through teaching and training. Education is a crucial thing in the development of a country. This study uses a qualitative descriptive type of research. This descriptive research has the purpose of providing an overview of a certain symptom, meaning that information about the symptoms to be studied is available which is then described in more detail and depth according to the research problem. TPACK (Technological Pedagogical Content Knowledge) is a conceptual that describes the combination of knowledge needed by an educator to integrate technology in learning effectively. This study shows that TPACK integration is already effective in this class. The use of short narrative videos as a learning medium has increased students' enthusiasm and engagement compared to previous learning methods. The implementation of TPACK has made the learning process more interesting, collaborative, and improved students' ability to absorb the material taught.